2014
DOI: 10.3109/10826084.2014.901389
|View full text |Cite
|
Sign up to set email alerts
|

Social Stressors and Alcohol Use Among Immigrant Sexual and Gender Minority Latinos in a Nontraditional Settlement State

Abstract: We sought to quantify the association of social stressors with alcohol use among immigrant sexual and gender minority Latinos in North Carolina (n = 190). We modeled any drinking in past year using logistic regression and heavy episodic drinking in past 30 days using Poisson regression. Despite a large proportion of abstainers, there were indications of hazardous drinking. Among current drinkers, 63% reported at least one heavy drinking episode in past 30 days. Ethnic discrimination increased, and social suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 68 publications
(71 reference statements)
0
25
0
Order By: Relevance
“…The remaining three papers reporting a positive association presented conflicting evidence. For example, two papers reported a positive association between sexual orientation discrimination and any drinking (Gilbert, Perreira, Eng, & Rhodes, 2014; Ortiz-Hernandez, Tello, & Valdes, 2009), but two additional papers found no such association (Rivers, 2004; Rosario, Schrimshaw, & Hunter, 2008). Further, in three papers sexual orientation discrimination was associated with hazardous drinking (Hequembourg & Dearing, 2013; Lehavot & Simoni, 2011; Weber, 2008); however, four papers found no relationship with hazardous drinking (D’Augelli, Grossman, Hershberger, & O’Connell, 2001; Igartua, Gill, & Montoro, 2003; M.W.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining three papers reporting a positive association presented conflicting evidence. For example, two papers reported a positive association between sexual orientation discrimination and any drinking (Gilbert, Perreira, Eng, & Rhodes, 2014; Ortiz-Hernandez, Tello, & Valdes, 2009), but two additional papers found no such association (Rivers, 2004; Rosario, Schrimshaw, & Hunter, 2008). Further, in three papers sexual orientation discrimination was associated with hazardous drinking (Hequembourg & Dearing, 2013; Lehavot & Simoni, 2011; Weber, 2008); however, four papers found no relationship with hazardous drinking (D’Augelli, Grossman, Hershberger, & O’Connell, 2001; Igartua, Gill, & Montoro, 2003; M.W.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a study of Latino men who have sex with men, discrimination was associated with increased risk of HIV infection due to increased sexual risk taking [36]. Discrimination has also been associated with increased substance use among Latinas and Latino men who have sex with men [3739], which can increase risk for STIs. Future research should explore whether discrimination is associated sexual health behaviors and utilization of health care among Latina sexual minority women.…”
Section: Discussionmentioning
confidence: 99%
“…While this phenomenon has been shown in multiple empirical studies of alcohol use among transgender populations (Bradford et al, 2013; Gilbert et al, 2014; Hotton et al, 2013; Reisner et al, 2013; Rowe et al, 2015), there is a paucity of research about how certain forms of assault (i.e., physical, verbal, and sexual) are associated with heavy episodic drinking for transgender people. In studies where transgender status was not measured, different types of victimization have diverse effects on alcohol use (Begle et al, 2011; Tyler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another study of Massachusetts adults (aged 18–64 years) found no differences in the prevalence of past-month heavy episodic use between transgender and cisgender populations (Conron et al, 2012). The remaining few studies about transgender individuals’ alcohol use utilized convenience-based samples or lacked direct cisgender comparison groups (Bradford et al, 2013; Gilbert et al, 2014; Hotton et al, 2013; Reisner et al, 2013; Rowe et al, 2015). Therefore, we have incomplete knowledge about drinking differences between transgender and cisgender populations, especially among young adults, the age group most at risk for heavy alcohol use in the United States (Centers for Disease Control and Prevention, 2010b; Fryar et al, 2006; Substance Abuse and Mental Health Services Administration, 2011; United States Department of Health and Human Services, 2009).…”
Section: Introductionmentioning
confidence: 99%